COMPARISON OF THE TRIASSIC LEGAL SYSTEM OF INDONESIA WITH THE FRENCH STATE - Afifulloh, Afifulloh; Sudarsono, Sudarsono; Hadiyantina, Shinta (TRUNOJOYO LAW REVIEW, 2022)
State law in Constitutional Law, there is an  object of regulation in which the system of the Triassic Concept of Politica, which is a normative principle that powers should not be handed over to the same person in order to prevent abuse of power by the ruling party.   Polotical triad offers a concept of state life by separating powers that are expected to be separated from each other in equal positions, so that they can control each other and balance each other (checks and balances), besides that the hope is that it can limit power so that there is no concentration of power on one hand which will later give birth to arbitrariness . The State of Indonesia with the State of France as a State of law (Civil Law), has similarities and differences in the application of the concept of Polotical triad. Similarities and differences in the application of the Polotical triad concept are material in comparing the systems applied in the Polotical triad concept. Comparison with the concept of Polotical triad between the State of Indonesia and the State of France, based on the 1945 Constitution of the Republic of Indonesia as the Constitution of the State of Indonesia and the Constitution of  Ocktober 4, 1958 as the Constitution of the State of France.